Mediterranean bee species, newly recorded in Slovenia (Hymenoptera: Apoidea) - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2009)
Five bee species are newly recorded in Slovenia: Lasioglossum laterale (Brullé, 1832), Andrena thomsoni Ducke, 1898, Melitta tomentosa Friese, 1900, Protosmia tiflensis (Morawitz, 1876) and Ceratina chalcites Germar, 1839. The food plants of the concerned bee species are reported.
Keywords: čebele; entomologija; favna; Slovenia; Slovenija